2014
DOI: 10.1016/j.jas.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Middle-to-Upper Palaeolithic site formation processes at the Bordes-Fitte rockshelter (Central France)

Abstract: Transformation in technological patterns associated with the Middle-to-Upper Palaeolithic transition between 50 and 40 ka in Western Europe and their relationship with the Neanderthal and Anatomically Modern Human populations and behaviors are issues that continue to stimulate heated debate. In this article we use the Middle and Early Upper Palaeolithic archaeo-stratigraphic record from the Bordes-Fitte rockshelter (les Roches d'Abilly site, Central France), a Bayesian analysis of the ages obtained by accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…'OD (%)' corresponds to the overdispersion determined with the CAM. For more details on the list of samples, the reader is Table 1 referred to Aubry et al (2012Aubry et al ( , 2014: samples 092201, -02, -03 and -04), Guérin et al (2015a: sample Intercomp;2015b: samples FER 3), Tribolo et al (in prep.,a: samples GDB 5,GDB 3;in prep.,b: samples EBC1 and EBC2); Urbanova (in prep. : samples Bdx 16045 to 16049), Lahaye et al (in press: samples BR-2011-32, -8, -15, -11).…”
mentioning
confidence: 99%
“…'OD (%)' corresponds to the overdispersion determined with the CAM. For more details on the list of samples, the reader is Table 1 referred to Aubry et al (2012Aubry et al ( , 2014: samples 092201, -02, -03 and -04), Guérin et al (2015a: sample Intercomp;2015b: samples FER 3), Tribolo et al (in prep.,a: samples GDB 5,GDB 3;in prep.,b: samples EBC1 and EBC2); Urbanova (in prep. : samples Bdx 16045 to 16049), Lahaye et al (in press: samples BR-2011-32, -8, -15, -11).…”
mentioning
confidence: 99%
“…Châtelperronian lithic technology is arguably one of the most well-studied and well-described of any of Europe's Middle to Upper Palaeolithic industries (Bricker and Laville, 1977;Boëda, 1991;Guilbaud, 1993;Pelegrin, 1995;Harrold, 2000;Connet, 2002Connet, , 2019Bordes, 2003;Roussel and Soressi, 2006;Grigoletto et al, 2008;Bachellerie, 2011;Bordes and Teyssandier, 2011b;Roussel, 2011;Soressi, 2011;Aubry et al, 2012Aubry et al, , 2014Baillet et al, 2014;Roussel et al, 2016b;Bodu et al, 2017;Discamps et al, 2019;Rios-Garaizar et al, 2022). Here, we combine primary data and observations from two Châtelperronian assemblages (Les Cottés, US 06 and Quinçay, En) with descriptions in the published literature to provide a detailed review of this technology.…”
Section: A Syntheac Review Of Châtelperronian Lithic Technologymentioning
confidence: 99%
“…The generally small thickness of blade platforms (~2-5mm), frequent soft abrasion of the external platform edge, ~90 exterior platform angles, common occurrence of splintered bulbs (esquillement de bulbe), weakly developed bulbs of percussion, and low frequency of pronounced internal platform 'lips' are consistent of a marginal application of force using a soft-stone hammer for plein debitage (e.g. Pelegrin, 1995;Bachellerie, 2011;Roussel et al, 2016;Bodu et al, 2017;Rios-Garaizar et al, 2022;Rios-Garaizar et al, 2012;Michel et al, 2019;Aubry et al, 2012;Aubry et al, 2014). Internal hard-hammer percussion is reported however, specifically for larger initialisation/maintenance products (Pelegrin, 2011) or the discrete production of blanks for end-scrapers (Michel et al, 2019).…”
Section: Percussor Type and Striking Gesturementioning
confidence: 99%
“…Therefore, reconstructing past climate changes at local‐ and regional‐scale spatial dimensions is necessary to deepen our understanding of Paleolithic activity in specific areas. Past climate changes can be inferred at Paleolithic sites using various proxies, including physical (e.g., lithological features, magnetic susceptibility, and grain size; Aubry et al, 2014; Bae, Li et al, 2018; Gribchenko, 2006; Hong et al, 2018; Liu et al, 2010; Shin et al, 2005) and biological (e.g., organic matter content, C/N ratio, and carbon isotope values) indicators. Earlier studies in Korea also suggested that carbon isotope values may help reconstruct past climate changes at Paleolithic sites (Hyun et al, 2015; Jha et al, 2020; Krajcarz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%